Cardiovascular Diseases in Sub-Saharan Africa Compared to High-Income Countries: An Epidemiological Perspective - Matthew Fomonyuy Yuyun; Karen Sliwa; Andre Pascal Kengne; Anna Olga Mocumbi; Gene Bukhman (Ubiquity Press, 2020)
Non-communicable diseases (NCDs) are the second common cause of death in sub-Saharan Africa (SSA) accounting for about 35% of all deaths, after a composite of communicable, maternal, neonatal, and nutritional diseases. Despite prior perception of low NCDs mortality rates, current evidence suggests that SSA is now at the dawn of the epidemiological transition with contemporary double burden of disease from NCDs and communicable diseases. In SSA, cardiovascular diseases (CVDs) are the most frequent causes of NCDs deaths, responsible for approximately 13% of all deaths and 37% of all NCDs deaths. Although ischemic heart disease (IHD) has been identified as the leading cause of CVDs mortality in SSA followed by stroke and hypertensive heart disease from statistical models, real field data suggest IHD rates are still relatively low. The neglected endemic CVDs of SSA such as endomyocardial fibrosis and rheumatic heart disease as well as congenital heart diseases remain unconquered. While the underlying aetiology of heart failure among adults in high-income countries (HIC) is IHD, in SSA the leading causes are hypertensive heart disease, cardiomyopathy, rheumatic heart disease, and congenital heart diseases. Of concern is the tendency of CVDs to occur at younger ages in SSA populations, approximately two decades earlier compared to HIC. Obstacles hampering primary and secondary prevention of CVDs in SSA include insufficient health care systems and infrastructure, scarcity of cardiac professionals, skewed budget allocation and disproportionate prioritization away from NCDs, high cost of cardiac treatments and interventions coupled with rarity of health insurance systems. This review gives an overview of the descriptive epidemiology of CVDs in SSA, while contrasting with the HIC and highlighting impediments to their management and making recommendations. Highlights: - The burden of non-communicable diseases including cardiovascular diseases is rising in SSA. - Levels of hypertension diagnosis, treatment, and control are low at <40%, <35%, and 10-20%, respectively, and more than 40% of patients with diabetes are not aware of their diagnosis in SSA. - SSA has 23% of the world's prevalent rheumatic heart disease cases. - The leading causes of heart failure in SSA are hypertensive heart disease, cardiomyopathy, and rheumatic heart disease, with ischemic heart disease accounting for <10% of cases compared to >50% in high-income countries.